Microplastics in the digestive tracts of commercial fish from the marine ranching in east China sea, China. (September 2020) - Wu, Jinghang; Lai, Mingxiang; Zhang, Yaowen; Li, Jingjing; Zhou, Hanghai; Jiang, Rijin; Zhang, Chunfang
Abstract: Microplastics are emerging pollutants in aquatic and terrestrial environment. Monitoring the ingestion of microplastics by fish in the environment is crucial to understanding the risks posed by microplastics in the marine ecosystem. In this study, we investigated the ingestion of microplastics in commercial fish from the marine ranching in Ma'an Archipelago. Samples were taken in 13 sites where 125 fishes belonging to 24 species and three feeding habits were captured. Presence of microplastics was verified in the 37.6% of fishes. The fiber represented the 90.74% of microplastics found. Blue (30%) and black (27%) were the most prevalent colors. The average abundance of microplastics in the digestive tracts of sampled fish was 0.43 ​± ​0.69 items/individual. In addition, cellophane and cellulose were the most abundant types of microplastics identified. Our results provided useful information for evaluating the environmental risks posed by microplastics in China from the marine organisms' angle. Highlights: Microplastics in commercial fishes in artificial reefs were reported. Fiber-shaped, blue particles were the most common types. Cellophane and cellulose were the most dominant polymer types in fish. A total of 54 microplastics were found in digestive tracts of 125 fishes.